2020
DOI: 10.1093/braincomms/fcaa124
|View full text |Cite
|
Sign up to set email alerts
|

Immunity in amyotrophic lateral sclerosis: blurred lines between excessive inflammation and inefficient immune responses

Abstract: Despite wide genetic, environmental and clinical heterogeneity in amyotrophic lateral sclerosis, a rapidly fatal neurodegenerative disease targeting motoneurons, neuroinflammation is a common finding. It is marked by local glial activation, T cell infiltration and systemic immune system activation. The immune system has a prominent role in the pathogenesis of various chronic diseases, hence some of them, including some types of cancer, are successfully targeted by immunotherapeutic approaches. However, various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 274 publications
3
78
0
Order By: Relevance
“…More than 50 genes are associated with ALS development and code for proteins involved in several molecular and cellular mechanisms, such as dysregulation of protein aggregates degradation, mitochondrial dysfunction, and impairment of axonal signaling. [ 110 ] A common feature of various ALS forms is the systemic inflammation, which leads to neuronal death and ALS motor deficits. [ 111 ] Gut microbial imbalance contributes to increase the pro‐inflammatory state and the severity of the disease.…”
Section: Immune Communication From Microbiota To Cns‐resident Cellsmentioning
confidence: 99%
“…More than 50 genes are associated with ALS development and code for proteins involved in several molecular and cellular mechanisms, such as dysregulation of protein aggregates degradation, mitochondrial dysfunction, and impairment of axonal signaling. [ 110 ] A common feature of various ALS forms is the systemic inflammation, which leads to neuronal death and ALS motor deficits. [ 111 ] Gut microbial imbalance contributes to increase the pro‐inflammatory state and the severity of the disease.…”
Section: Immune Communication From Microbiota To Cns‐resident Cellsmentioning
confidence: 99%
“…While neuroinflammation is uniformly present in end-stage pathology and is recognized as a major player in ALS progression [ 28 ], how and when it occurs remains unclear due to a lack of studies investigating this phenomenon in early disease and over the duration of the disease [ 29 ]. In fact, it was recently suggested that initial pre-symptomatic and early symptomatic phases are dominated by anti-inflammatory immune responses, whereas late symptomatic and terminal stages are dominated by proinflammatory immune responses [ 30 ]. This theory could actually explain the absence of KP modification found at early stages (diagnosis) in ALS patients, while most intermediates tend to be higher in ALS subjects with more severe evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with previous studies that identified higher ratios of neutrophils and/or granulocytes to lymphocytes in ALS patients 69,70 , elevated levels of inflammatory proteins 71 , and an association between higher neutrophil proportions and worse prognosis 72 . Although immune alterations could be part of a systemic aspect of ALS, there is evidence that suggests that the peripheral immune system contributes to neuroinflammation, the latter being an established phenomenon in ALS as well as other neurodegenerative diseases 73,74 . Especially interesting in this regard is that recent evidence shows that mast cells infiltrate skeletal muscles at the neuromuscular junction and degranulate to help recruit neutrophils 75,76 , which prevent reinnervation capacity and may thus be a potential mechanism causing worse prognosis.…”
Section: Discussionmentioning
confidence: 99%